(untitled) (Conferencea, 2023)
In philosophy, the subject of much debate is the human problem. The relevance of the human question is that philosophy is formed on the basis of the subject-object relationship, and the subject side is a "thinking being". i.e. "man" constitutes. Moreover, the "problem of man" has always been a central issue in both Western and Eastern philosophy, including the philosophy of the Greek philosopher Socrates and the philosophy of the first Muslim philosopher Kindi. This article talks about the ideas of man and his essence, expressed by Farobi.